In vivo anthelmintic activity of hydroethanolic extract of Piper cubeba fruits in sheep naturally infected with gastrointestinal nematodes - de Araújo Sanchez, Clara [UNESP]; Gonçalves, Juliana Alencar [UNESP]; Andrade e Silva, Márcio Luís; Rodrigues, Maria Gabriela Fontanetti [UNESP]; Santos, Fernanda Amorim [UNESP]; da Silva de Laurentiz, Rosangela [UNESP]; Gomes de Soutello, Ricardo Velludo [UNESP] (Elsevier, 2025)
Parasitic infections caused by gastrointestinal nematodes (GINs) are the main cause of production losses in small ruminants, especially sheep. Haemonchus contortus is the most common nematode in tropical regions. The indiscriminate use of synthetic anthelmintics to control helminthosis has led to the development of resistant parasites. As a result, there has been growing interest in using plant extracts and natural products to control gastrointestinal nematodes in sheep. Therefore, this study aimed to evaluate the in vivo anthelmintic activity of the hydroethanolic extract of Piper cubeba fruit in sheep naturally infected with gastrointestinal nematodes. Initially, an experiment was conducted where the Piper cubeba extract was administered at a dose of 2.5 mg/kg body weight three times at 7-day intervals. For this, 18 animals were divided into three groups: a control group, a group treated with levamisole phosphate at 4.7 mg/kg body weight subcutaneously, and a group treated with Piper cubeba extract, which was administered in pure form orally to the animals through a cannula. Based on the results of this experiment, a second experiment was conducted using the same experimental design and same extract, but the effectiveness of the extract was evaluated at a single dose of 5.0 mg/kg body weight administered on day 0. The determination of biochemical parameters for the group treated with extract and the identification of nematode species for all groups were performed on different days of this experiment. The results of the first experiment showed that the extract reduced the FEC by 84 % on day 7 and 83 % on day 35 compared to the control group. These results prompted a second experiment, using the same experimental design, but with the extract administered to the animals in a single dose of 5 mg/kg body weight. The result for the reduction in FEC in the levamisole-treated group was similar to that obtained in the first experiment, whereas in the group treated with a single dose of the extract, the reduction was significant from day 7, reaching 97 % by day 35 compared to the control group, with no significant difference from the levamisole-treated group. Regarding nematode species, on day 0, all treatments in the experiment showed a predominance of Haemonchus contortus, but other species such as Cooperia, and Oesophagostomum were also identified. On day 35, only Haemonchus contortus was identified in the extract-treated group and the levamisole-treated group, whereas Cooperia and Oesophagostomum species were also found in the control group. Toxicity tests for liver and kidney functions showed no alterations after administration of the single dose extract. These results demonstrate the in vivo anthelmintic activity of the hydroethanolic extract of Piper cubeba fruits and suggest its potential use as an alternative to synthetic chemicals in controlling parasites in sheep.
Keywords: Gastrointestinal nematodes; Natural products; Piper cubeba; Plant extract; Small ruminants